Trust and Moral Conflict in “The Idiot” - Lagerspetz, Olli (Åbo Akademis förlag, 2025)
Hugo Strandberg came to the Åbo Philosophy department in the 2000s. If my memory is correct, he came on a grant to write a work on that philosophical super-topic: the meaning of life. He joined the regular teaching staff in the early 2010s, and since then, he has also spent several years teaching and writing at the Pardubice Ethics Centre in the Czech Republic. He has been a valuable resource in Åbo (and in Pardubice) because of his wide and penetrating knowledge of philosophical literature. He is a dependable and knowledgeable colleague. However, thinking of my own philosophical exchanges with him, my greatest benefit has come from his innovative and somewhat irreverent attitude to the materials that he knows so well. A philosophical “school” is, at its worst, a mutual admiration society, where some few arguments, themes and texts make the rounds year after year. On the other hand, a productive philosophical milieu is one where philosophers maintain discussions to develop shared insights each in their own way. Hugo is hardly a member of a philosophical school in the narrow sense, but he contributes to a philosophical milieu. One typical feature of the milieus where he has been active is attention to the philosophical relevance of novels and films. (Hugo, unlike myself, is an active member of the philosophy film club.) In this contribution to his Festschrift, I seize the opportunity to develop a theme I have discussed with Hugo. Prince Myshkin, of Dostoevsky’s Idiot (1946, first published 1868), has been part of my philosophical and personal life for more than three decades now but, apart from an early misguided attempt that never made it to a publisher, I have not previously written an essay on that powerful novel.